Enhancing Service Improvement and performance at the National Institute of Public Health of Kosova (Bangladesh Journal of Medical Science, 2026)
Background Public health experts deal with the assessment of the health needs of the population and provide professional expertise to decision-makers regarding the prioritization of health problems, the distribution of resources, and the design of health policies. Aim The aim of this research is to measure and increase the performance of the National Institute of Public Health (NIPH) of as well as design strategic plann based on SWOT analysis. Methodology The research is cross-sectional analysis and prospective planning. The triangulation method regarding the selfassessment of work achievements was carried out. The micro and meso levels of analysis were used for evaluation. SWOT analysis was used at the departmental level as well as the nominal group technique with the board of National Institute of Public Health (NIPH). Results SWOT analysis enabled the development of strategic plans to achieve SMART goals. The activities were categorized into four groups: human resources (HR), continuous professional development (CPD), organizational issues (OI), and material resources (MR). Three OI activities were prioritized at the top level because they were high impact–low effort. The MR activity ‘Provision of means of transport’ was labeled a fourth-level priority, being low impact–high effort, while all other activities were labeled second-level priorities, being high impact–high effort. Conclusion: Continuous investment in public health is necessary for a functional health system because it is a key factor influencing disease prevention and life extension.BJMS, Vol. 25 No. 01 January’26 Page : 281-289